French interventionism in the Sahel: a flawed strategy, imperfect geopolitics - Lofti SOUR (Przegląd Geopolityczny)
Over the past few years, there has been a notable rise in French military involvement in Africa. Despite attempts to establish a more balanced post-colonial relationship and a significant reduction in its permanent military presence, France continues to be a highly sought-after participant in resolving security challenges in Africa. Despite French policymakers' repeated assurances that their role as the "gendarme of Africa" is a thing of the past, French troops have been engaged in nine military operations since the start of the new millennium. This paper aims to analyze French strategy in the Sahel region, with a particular focus on Operation Barkhane, in light of the changing French doctrine and practices.